Bevacizumab in Aggressive Pituitary Adenomas – Experience with 3 Patients - Osterhage, Katharina; Rotermund, Roman; Droste, Michael; Dierlamm, Judith; Saeger, Wolfgang; Petersenn, Stephan; Aberle, Jens; Flitsch, Jörg (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective To investigate bevacizumab as alternative treatment of aggressive pituitary adenomas after exhaustion of standard therapies.Design and Methods Retrospectively, 3 patients undergoing microscopic transsphenoidal surgery of aggressive pituitary adenomas from 2008 till 2018 that were treated with bevacizumab were identified. Development of disease and treatment were evaluated.Results Two patients suffered from ACTH-secreting adenomas, one from a non-functioning adenoma. All patients underwent multiple surgical, chemo- and radiotherapeutical approaches including temozolomide, showing favorable results in one patient. Deterioration of clinical condition in all patients led to an individual, palliative attempt of bevacizumab. Patients 1 and 2 showed a decrease of ACTH after first administrations, but therapy had to be ended shortly after due to a further deterioration of their condition. Patient 3 showed a stabilization of the disease for 18 months. Patients died 8, 15 and 7 years after initial diagnosis, respectively, and 2, 4, and 24 months after initiation of bevacizumab therapy, respectively.Conclusion The demonstrated results suggest a considerable effect of bevacizumab in aggressive pituitary adenomas. The advanced stage of disease in all three patients, the overall short period of administration and just one patient showing a clinical benefit do not allow a general statement on the effectiveness. At the current stage of clinical experience, an approach with bevacizumab can be considered as an individual palliative attempt of treatment, when standard treatments are exhausted. Our results underline the need for further studies to evaluate this drug as potential player in therapy resistant aggressive pituitary tumors.
Keywords: Pituitary adenoma; Cancer; Temozolomide; Bevacizumab; Hormones